2018
DOI: 10.1180/mgm.2018.85
|View full text |Cite
|
Sign up to set email alerts
|

Inclusions in an isoferroplatinum nugget from the Freetown Layered Complex, Sierra Leone

Abstract: Inclusions of platinum-group minerals (PGM) within alluvial isoferroplatinum nuggets from the Freetown Peninsula, Sierra Leone, are aligned with their shape determined by the structure of their host. The edges of the majority of the inclusions lie at 0°, 45° or 90° to external crystal edges of the nugget which shows that the inclusions are not randomly oriented earlier minerals incorporated within their host. The inclusions are later infills, probably formed at the surface of the nugget during growth and subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In evidence to the contrary, previous work [27,57] and the present review (e.g., Figure 3E,F) have shown that the (Pt,Pd)-bismuthotellurides and -tellurides are the PGM species most susceptible to oxidation/weathering and are unstable in the supergene environment. PGM of this mineral group and the equally unstable sulfarsenide inclusions have only survived oxidation as they are well-shielded by the enclosing Pt-Fe alloy grain, and the described multi-PGM assemblage [98] as well as their Pt-Fe alloy host are definitely not products of supergene formation. Concentration of rare and stray elements should follow a chemical gradient which is not in evidence in this environment.…”
Section: Pgm In Placersmentioning
confidence: 95%
See 3 more Smart Citations
“…In evidence to the contrary, previous work [27,57] and the present review (e.g., Figure 3E,F) have shown that the (Pt,Pd)-bismuthotellurides and -tellurides are the PGM species most susceptible to oxidation/weathering and are unstable in the supergene environment. PGM of this mineral group and the equally unstable sulfarsenide inclusions have only survived oxidation as they are well-shielded by the enclosing Pt-Fe alloy grain, and the described multi-PGM assemblage [98] as well as their Pt-Fe alloy host are definitely not products of supergene formation. Concentration of rare and stray elements should follow a chemical gradient which is not in evidence in this environment.…”
Section: Pgm In Placersmentioning
confidence: 95%
“…In contrast, a secondary origin of PGM in placers and soils is anticipated by several authors [81,[91][92][93][94][95][96][97][98]. As size, shape, composition and micro texture of many eluvial and alluvial PGM differ from those observed in bedrocks and ores, it was proposed that secondary PGM come into being in a simplified process: (1) Serpentinization or weathering leads to the decomposition of base-metal sulfides carrying PGE in solid solution; (2) PGE are removed and transported as colloidal particles; (3) The colloids may coalesce or accrete to form larger particles and aggregates of PGE alloys.…”
Section: Pgm In Placersmentioning
confidence: 99%
See 2 more Smart Citations
“…One of these (McCreesh et al, 2018) concerns the 'Waterberg Project', currently under exploration by Platinum Group Metals Ltd in the northern limb of the ∼2.05 Ga Bushveld Complex (South Africa). The second is a detailed study of placer PGM nuggets derived from the ∼193 Ma Freetown Layered Complex, Sierra Leone (Bowles et al, 2018). Thirdly, Augé et al (2018) describe the mineralogy and geochemistry of PGM from mineralized horizons in the ∼200 Ma Conakry Igneous Complex (Guinea).…”
mentioning
confidence: 99%